Answer:
Option B
Explanation:
Using the law of logarithms
![n log x= log x^(n)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r0ew2l934nzygqslili4c3t8q2sk1vzkre.png)
Therefore, since all the logs are to the same base, I will assume the base.
Also, when the bases are the same
log y+ log x= log (x+y)
![\frac {1}{2}(log 4+ log 16)=log 4^(0.5)+log 16^(0.5)=log 2+log 4=log 6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/efv15z0s8v87uocyoqer4znovwde9jsofz.png)
Now log 6-log 2= log (6-2)= log 4
Therefore, option B is correct